PEMANFAATAN EKSTRAK BUNGGA TELANG (Clitoria Ternatea Linn) DALAM PAKAN IKAN UNTUK MENINGKATKAN KECERAHAN IKAN KOI KOHAKU (Cyprinus carpio) - Handajani, Hany; Arianto, Doddy; Zubaidah, Anis (Jurnal Perikanan Unram, 2025)
One of the biodiversity that Indonesia has and should be proud of is the diversity of freshwater ornamental fish species, one of which is koi kohaku fish (Cyprinus carpio). The purpose of this study was to determine the effect of color in telang flower extract to improve the color quality of koi kohaku fish and to determine the best dose of telang flower extract in improving the color of koi fish. This study used 4 different treatments, namely A (10%) bayang flower extract, B (15%) bayang flower extract, C (20%) bayang flower extract, and D (control). The parameters observed were the brightness of fish color, final weight, length growth, SR, and water quality, which will be analyzed using ANOVA. Measuring fish color using a modified toca color finder (M-TCF) tool where this tool has a color column column marked with a score value from 1 - 60. The results of this study indicate that the addition of telang flower extract to commercial feed affects the color quality of koi kohaku fish. The quality of color severity in Kohaku koi fish is highest in treatment C (20%) with a score value of 35 on fish color, for treatment D (control), B (15%), and A (10) each has a score value of 32, 34, 33 on fish color. Mixing bayang flower extract into commercial feed can improve the color of koi kohaku fish, the best color improvement was found in the treatment of adding 20% bayang flower extract.